Genetic characterization of isolates of the basidiomycete Agaricus blazei by RAPD - Colauto,Nelson Barros (2002)
The genetic divergence of five isolates of Agaricus blazei was determined based on RAPD data. Results indicate that there is little genetic variability among the commercialized strains and that RAPD is a feasible and low cost technique that can be used to characterize this fungus.